E. coli NF73-1 Isolated From NASH Patients Aggravates NAFLD in Mice by Translocating Into the Liver and Stimulating M1 Polarization - Zhang, Yifan; Jiang, Weiwei; Xu, Jun; Wu, Na; Wang, Yang; Lin, Tianyu; Liu, Yun; Liu, Yulan (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: The gut microbiota is associated with nonalcoholic fatty liver disease (NAFLD). We isolated the Escherichia coli strain NF73-1 from the intestines of a NASH patient and then investigated its effect and underlying mechanism. Methods: 16S ribosomal RNA (16S rRNA) amplicon sequencing was used to detect bacterial profiles in healthy controls, NAFLD patients and NASH patients. Highly enriched E. coli strains were cultured and isolated from NASH patients. Whole-genome sequencing and comparative genomics were performed to investigate gene expression. Depending on the diet, male C57BL/6J mice were further grouped in normal diet (ND) and high-fat diet (HFD) groups. To avoid disturbing the bacterial microbiota, some of the ND and HFD mice were grouped as “bacteria-depleted” mice and treated with a cocktail of broad-spectrum antibiotic complex (ABX) from the 8th to 10th week. Then, E. coli NF73-1, the bacterial strain isolated from NASH patients, was administered transgastrically for 6 weeks to investigate its effect and mechanism in the pathogenic progression of NAFLD. Results: The relative abundance of Escherichia increased significantly in the mucosa of NAFLD patients, especially in NASH patients. The results from whole-genome sequencing and comparative genomics showed a specific gene expression profile in E. coli strain NF73-1, which was isolated from the intestinal mucosa of NASH patients. E. coli NF73-1 accelerates NAFLD independently. Only in the HFD-NF73-1 and HFD-ABX-NF73-1 groups were EGFP-labeled E. coli NF73-1 detected in the liver and intestine. Subsequently, translocation of E. coli NF73-1 into the liver led to an increase in hepatic M1 macrophages via the TLR2/NLRP3 pathway. Hepatic M1 macrophages induced by E. coli NF73-1 activated mTOR-S6K1-SREBP-1/PPAR-α signaling, causing a metabolic switch from triglyceride oxidation toward triglyceride synthesis in NAFLD mice. Conclusions: E. coli NF73-1 is a critical trigger in the progression of NAFLD. E. coli NF73-1 might be a specific strain for NAFLD patients.